Disparate HDV ribozyme crystal structures represent intermediates on a rugged free-energy landscape - Sripathi, Kamali N; Tay, Wendy W; Banáš, Pavel; Otyepka, Michal; Šponer, Jiří; Walter, Nils G (RNA (New York, N.Y.), 2014)
The hepatitis delta virus (HDV) ribozyme is a member of the class of small, self-cleaving catalytic RNAs found in a wide range of genomes from HDV to human. Both pre- and post-catalysis (precursor and product) crystal structures of the cis-acting genomic HDV ribozyme have been determined. These structures, together with extensive solution probing, have suggested that a significant conformational change accompanies catalysis. A recent crystal structure of a trans-acting precursor, obtained at low pH and by molecular replacement from the previous product conformation, conforms to the product, raising the possibility that it represents an activated conformer past the conformational change. Here, using fluorescence resonance energy transfer (FRET), we discovered that cleavage of this ribozyme at physiological pH is accompanied by a structural lengthening in magnitude comparable to previous trans-acting HDV ribozymes. Conformational heterogeneity observed by FRET in solution appears to have been removed upon crystallization. Analysis of a total of 1.8 µsec of molecular dynamics (MD) simulations showed that the crystallographically unresolved cleavage site conformation is likely correctly modeled after the hammerhead ribozyme, but that crystal contacts and the removal of several 2'-oxygens near the scissile phosphate compromise catalytic in-line fitness. A cis-acting version of the ribozyme exhibits a more dynamic active site, while a G-1 residue upstream of the scissile phosphate favors poor fitness, allowing us to rationalize corresponding changes in catalytic activity. Based on these data, we propose that the available crystal structures of the HDV ribozyme represent intermediates on an overall rugged RNA folding free-energy landscape.
Keywords: RNA Cleavage; RNA, Catalytic; RNA, Viral; time-resolved FRET; RNA virová; krystalografie rentgenová; simulace molekulární dynamiky; Nucleic Acid Conformation; RNA malá jaderná; RNA, Small Nuclear; Fluorescence Resonance Energy Transfer; Molecular Dynamics Simulation; conformational change; small ribozyme; molekulární modely; Crystallography, X-Ray; virus hepatitidy delta; Models, Molecular; katalýza; konformace nukleové kyseliny; kinetika; Hepatitis Delta Virus; steady-state FRET; Catalytic Domain; štěpení RNA; rezonanční přenos fluorescenční energie; Catalysis; molecular dynamics simulation; Kinetics; RNA katalytická; katalytická doména